Faktor-Faktor yang Berhubungan dengan Abortus Inkomplit di Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau - Risa Pitriani (STIKes Hang Tuah Pekanbaru, 2013)
Incomplete abortion is termination of pregnancy in which the products of conception are not entirely expelled or removed from uterus, before 20 weeks in pregnancy. Approximately 90% of deaths due to abortion complications This casecontrol study was designed to determine association factors with incidence of incomplete abortion at Arifin Achmad General Hospital 2010-2012. the event spending most of the products of conception in pregnancy before 20 weeks, there was still some left in the uterus. Approximately 90% of deaths due to abortion complications. The purpose of research is knowing the factors associated with the incidence of incomplete abortion at the Arifin Achmad Hospital in Riau Province Year 2010-2012. Type of case-control study design. Cases were pregnant women who had incomplete abortion and normal controls were pregnant women who did not experience an incomplete abortion were â‰¤ 20 weeks in hospitals Arifin Achmad Pekanbaru 2010-2012. The results were significantly associated variables, namely: 1) mothers with low education 1,469 times more at risk of experiencing an incomplete abortion than women who have a higher education (95% CI: OR = 1.067 to 2.024), 2) maternal pregnancy spacing <2 years 2,084 times the risk of having incomplete abortion compared, mothers who have gestational distance â‰¥ 2 years (CI 95%: OR = 1.507 to 2.881), 3) mothers who work 4,184 times more at risk of experiencing an incomplete abortion than women who did not work (95% CI: OR = 2.657 to 6.588); variable is inversely related to hemoglobin and parity, and the confounding variable is the age of the parity. As Cconclusion, education, spacing of pregnancy and occupation have causal relationship with the incidence of incomplete abortion.that the independent variables that have a causal relationship with the incidence of incomplete abortion is variable, distance education and employment pregnancy. Confounding variable is the variable age-related incidence of parity on the incidence of incomplete abortion. This study suggests to improve knowledge about complication abortion and plan pregnancy. Advice for pregnant women to know the danger signs of TM I and set the distance kehamialan to avoid incomplete abortion; to the next researcher to observe Hb and maternal parity before through books KIA, and maternal age> 35 years in an effort so that no pregnant at parity > 3